Dwa bieguny filmowych afordancji w literaturze XXI wieku = Two poles of film affordances in the literature of the 21st century - Ślósarz, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Literary film affordances, i.e. the ways in which literature refers to film, include citing names of actors, names of movie heroes, and film titles; they include also reflections on the role of film in society, on the ways in which it is received by the viewers, on the characteristics of the audience, etc. 214 literary texts - poems, short stories, novels and drama - from the 21st century have been scanned with the use of "Adobe Fine Reader 12" programme in search of the word "film".
Keywords: afordancje filmu literackiego; bohater filmowy; widz; imperializm kulturowy; demokratyzacja; propaganda; postawa konsumpcyjna; nieautentyczność; literary film affordances; movie heroes; viewers; watching movies; sensing danger; cultural imperialism; democratization; consumerist attitude